Spin Effect on Oxygen Electrocatalysis. Issue 8 (5th May 2021) - Li, Jisi; Ma, Jingjing; Ma, Ziang; Zhao, Erling; Du, Kun; Guo, Jiaxin; Ling, Tao
Abstract : Oxygen involved reactions, including oxygen reduction (ORR) and oxygen evolution reactions (OERs), play a key role in electrochemical energy devices, such as fuel cells and metal–air batteries. Recent theoretical calculations and experimental investigations reveal that the energy loss in ORR/OER is closely related to the triplet O2 generation/conversion step. However, the spin‐related phenomena have long been neglected in understanding of the ORR/OER mechanism. This review highlights recent advances in understanding and application of the spin‐related effect in oxygen electrocatalysis. It is demonstrated that the exchange interaction in magnetic catalysts can build a spin‐selective channel to filter the electron spins with appropriate orientation in the O2 generation/conversion step during ORR/OER. It is believed that the introduction of spin effect can establish a more comprehensive understanding of oxygen electrocatalysis and assist designing more reactive oxygen electrocatalysts. Abstract : How can the activity of the catalyst near the top of the volcano plots be further improved beyond the volcano peak? This review focuses on recent progress in understanding the spin‐related effect to optimize the reaction enthalpy and entropy of oxygen electrocatalysis, which can help design super active oxygen electrocatalysts.